Use of protein cross-linking and radiolytic footprinting to elucidate PsbP and PsbQ interactions within higher plant Photosystem II - Mummadisetti, Manjula P. (Proc Natl Acad Sci U S A, 2014)
Protein cross-linking and radiolytic footprinting coupled with high-resolution mass spectrometry were used to examine the structure of PsbP and PsbQ when they are bound to Photosystem II. In its bound state, the N-terminal 15-amino-acid residue domain of PsbP, which is unresolved in current crystal structures, interacts with domains in the C terminus of the protein. These interactions may serve to stabilize the structure of the N terminus and may facilitate PsbP binding and function. These interactions place strong structural constraints on the organization of PsbP when associated with the Photosystem II complex. Additionally, amino acid residues in the structurally unresolved loop 3A domain of PsbP ((90)K–(107)V), (93)Y and (96)K, are in close proximity (≤11.4 Å) to the N-terminal (1)E residue of PsbQ. These findings are the first, to our knowledge, to identify a putative region of interaction between these two components. Cross-linked domains within PsbQ were also identified, indicating that two PsbQ molecules can interact in higher plants in a manner similar to that observed by Liu et al. [(2014) Proc Natl Acad Sci 111(12):4638–4643] in cyanobacterial Photosystem II. This interaction is consistent with either intra-Photosystem II dimer or inter-Photosystem II dimer models in higher plants. Finally, OH(•) produced by synchrotron radiolysis of water was used to oxidatively modify surface residues on PsbP and PsbQ. Domains on the surface of both protein subunits were resistant to modification, indicating that they were shielded from water and appear to define buried regions that are in contact with other Photosystem II components.